THE EXTREME VULNERABILITY OF SMALLHOLDER FARMERS OF CHANGING CLIMATE ALONG WITH ITS EFFECT UPON THE PRODUCTION: EVIDENCE FROM NIGERIA - Belewu, K.Y.; Kotila, V.A.; Bello, K.A.; Kadir, R.A.; Mohammed, S.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The research examined the extreme vulnerability of smallholder farming households in Kwara State, Nigeria. Primary data were gathered and analyzed using descriptive statistics, multiple regression models, and a Likert-type scale. Findings indicate that 65.83% of the respondents were aged 50 years and above, 55.83% were male, and 59.17% had attained tertiary education. Furthermore, 74.17% of the participants reported being aware of the changing climate, 60.83% had individual experiences with it, and 59.17% had experienced flooding in their communities. The consequence of changing in climate on lower crop yields as part of productivity in agriculture (4.30), increased food shortages (4.14), pest infestations and disease outbreaks (4.13). Key factors significantly influencing farmers' vulnerability to climate change included age, education level, farm size and awareness of climate change were positively significant at 1%. While contact with extension agents, flooding experiences, and exposure to pests and diseases were negatively significant at 1% and 5% respectively. According to the survey, 48.33% of participants had a moderate level of climate change vulnerability. Coping strategies identified included tree planting to prevent flooding, obtaining farm insurance, constructing drainage systems, cultivating climate-resilient crops, and farmer sensitization programs. The study concludes that majority of smallholder farming households in study arear are susceptible to climate change. It recommends that agricultural extension agents be thoroughly educated on climate change and its effect on farming to be able to effectively disseminate relevant details to farmers.